Pengungkapan Corporate Social Responsibility (CSR) pada Perusahaan Sektor Industri Dasar dan Kimia di Indonesia - Merry Anna Napitupulu; Rike Yolanda Panjaitan (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2018)
This research was conducted to analyze the disclosure of Corporate Social Responsibility (CSR) in companies of Basic Industrial and Chemical sectors in Indonesia. The research is expected to be able to provide the latest information and trends regarding CSR disclosures in Basic Industries and Chemistry in Indonesia. The population in this study were all basic industrial and chemical sector companies listed on the Indonesia Stock Exchange (BEI) in 2013-2015. The total sample in this study is 172 annual reports of basic industrial and chemical sector companies in Indonesia. This research is a quantitative descriptive study using content analysis method with index approach and narrative disclosure. The results of this study indicate that the quantity and quality of information on CSR disclosure is still very low. The quantity and quality of information on CSR disclosures in basic industrial and chemical sector companies in Indonesia has increased every year starting from 2013-2015. Almost all companies in the basic and chemical industrial sectors carry out CSR disclosures in Indonesia in annual reports every year in the 2013-2015 period. The social category sub categories of employment and work comfort are considered as the most important disclosure categories disclosed by the company in the annual report. Metal sub-sectors and similar products are industrial subsectors that have the highest total value of quantity and quality of CSR disclosure.